Purification and Characterization of Gibberellic Acid-Induced Cysteine Endoproteases in Barley Aleurone Layers - Koehler, Susan (1988)
Using in series ammonium sulfate precipitation, gel filtration, and DEAE anion exchange high performance liquid chromatography, we have purified to homogeneity a protease of M(r) 37,000 secreted from barley (Hordeum vulgare L. cv Himalaya) embryoless half-seeds. This protease exists in three isozymic forms whose synthesis and secretion from barley aleurone layers was shown to be a gibberellic acid (GA(3))-dependent process (R Hammerton, T-HD Ho 1986 Plant Physiol 80: 692-697). This protease constitutes a major portion of the protease activity secreted from half-seeds between 72 to 96 hours of incubation in the presence of GA(3) as detected on activity gels containing hemoglobin as the substrate. Analysis of digestion products by urea/sodium dodecyl sulfate-polyacrylamide gel electrophoresis and gel filtration indicated that this protease is an endoprotease, therefore it is designated as barley endoprotease-A (EP-A). Inhibitor studies demonstrated that EP-A belongs to the cysteine class of endoproteases. The optimum pH for EP-A activity was 5.0, and the temperature optimum was 45°C. Comparison of cyanogen bromide generated peptide fragments and NH(2)-terminal sequence analyses of the three individual EP-A isozymes demonstrates that they are very similar to each other. The NH(2)-terminal sequence shows extensive sequence homology to the NH(2)-terminal sequence of papain and several other cysteine proteinases. We also provide evidence that EP-A is not `aleurain,' a putative cysteine proteinase encoded by a GA(3)-induced barley cDNA clone (JC Rogers, D Dean, GR Heck 1985 Proc Natl Acad Sci USA 82:6512-6516).